Do Skills Acquired from Training with a Wire Navigation Simulator Transfer to a Mock Operating Room Environment?. Issue 10 (October 2019) - Long, Steven A.; Thomas, Geb; Karam, Matthew D.; Anderson, Donald D.
Abstract: Background: Skills training and simulation play an increasingly important role in orthopaedic surgical education. The intent of simulation is to improve performance in the operating room (OR), a trait known as transfer validity. No prior studies have explored how simulator-based wire navigation training can transfer to higher-level tasks. Additionally, there is a lack of knowledge on the format in which wire navigation training should be deployed. Questions/purposes: (1) Which training methods (didactic content, deliberate practice, or proficiency-based practice) lead to the greatest improvement in performing a wire navigation task? (2) Does a resident's performance using a wire navigation simulator correlate with his or her performance on a higher-level simulation task in a mock OR involving a C-arm, a radiopaque femur model, and a large soft tissue surrogate surrounding the femur? Methods: Fifty-five residents from four different medical centers participated in this study over the course of 2 years. The residents were divided into three groups: traditional training (included first-year residents from the University of Iowa, University of Minnesota, and the Mayo Clinic), deliberate practice (included first-year residents from the University of Nebraska and the University of Minnesota), and proficiency training (included first-year residents from the University of Minnesota and the Mayo Clinic). Residents in each group received a didactic introduction covering the task of placing a wire to treat an intertrochanteric fracture, and this was considered traditional training. Deliberate practice involved training on a radiation-free simulator that provided specific feedback throughout the practice sessions. Proficiency training used the same simulator to train on specific components of wire navigation, like finding the correct starting point, to proficiency before moving to assessment. The wire navigation simulator uses a camera system to track the wire and provide computer-generated fluoroscopy. After training, task performance was assessed in a mock OR. Residents from each group were assessed in the mock OR based on their use of fluoroscopy, total time, and tip-apex distance. Correlation analysis was performed to examine the relationship between resident performance on the simulator and in the mock OR. Results: Residents in the two simulation-based training groups had a lower tip-apex distance than those in the traditional training group (didactic training tip-apex distance: 24 ± 7 mm, 95% CI, 20–27; deliberate practice tip-apex distance: 16 ± 5 mm, 95% CI, 13–19, p = 0.001; proficiency training tip-apex distance: 15 ± 4 mm, 95% CI, 13–18, p < 0.001). Residents in the proficiency training group used more images than those in the other groups (didactic training: 22 ± 12 images, p = 0.041; deliberate practice: 19 ± 8 images; p = 0.012, proficiency training: 31 ± 14 images). In the two simulation-based training groups, resident performance on the simulator, that is, tip-apex distance, image use, and overall time, was correlated with performance in the mock OR (r-square = 0.15 [p = 0.030], 0.61 [p < 0.001], and 0.43 [p < 0.001], respectively). Conclusions: As residency programs are designing their curriculum to train wire navigation skills, emphasis should be placed on providing an environment that allows for deliberate practice with immediate feedback about their performance. Simulators such as the one presented in this study offer a safe environment for residents to learn this key skill. Level of Evidence: Level II, therapeutic study.